The Role of Management Information System in Employee Career Development Decision Making at PT. PLN (Persero) UP3 Manado - Koropit, Intansia; Mawuntu, Priska Shirty Thelma; Ferdinandus, Aprildy (Universitas Diponegoro, 2023)
Management Information System is a system that is used in the processing and organizing of data and information that has been used to support the overall management processes of an organization. With a good system, the leadership can obtain data regarding work experience, position experience, job performance, loyalty, and other information that can support the decision-making process including employee career development. This study aims to figure out the role of the Employee Performance Management Information System (SIMKP) in the decision-making of employee career development at PT. PLN (Persero) UP3 Manado. The qualitative research design with a case study approach was carried out at PT. PLN (Persero) UP3 Manado, from February to April 2022. Data collection techniques used were observations and interviews. The results of this study were there are three stages of the role of MIS in decision making of career development. The intelligence stage helps in collecting the data needed in the decision making of employee career development process, the design stage helps in processing and analyzing existing the data to be used in the employee career development decision-making process, and the choice stage helps in determining choices from various alternatives in the employee career development decision-making process. It can be concluded that there are three stages in which SIMKP plays a role in the career development decision-making process of employees in PT. PLN (Persero) UP3 Manado